2021
DOI: 10.9734/jpri/2021/v33i32b31764
|View full text |Cite
|
Sign up to set email alerts
|

Immunoboosting Potential of Spices with Special Reference to North East India against the Novel Coronavirus Pandemic- A Review

Abstract: Spices, which is key ingredient in every household products not only used for adding aroma to food but however, has health promoting and protective activity against foreign pathogens. Different spices used in day to day life boosts the immune system that leads to healthy and prosperous life. The commonly used spices not only have antimicrobial or antiviral activity, but also serve as a rich source of various vitamins, minerals, antioxidants etc. The medicinal importance of spices dates from ancient Ayurveda an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The antioxidant and anti-Alzheimer activities of the crude methanolic extract of Celastrus paniculatus seeds were investigated. The extracts scavenged DPPH free radicals, inhibited peroxynitrite (ONOO−), and reduced ROS production [128] Coriandrum sativum In the tropical and subtropical region, Pakistan, and all South-East Asian countries [129] Ficus carica South Asian to Easter pedestrian Mesocarp and endocarp metabolites scavenged ROS. NMR profiling showed that aliphatic chemicals like γ-sitosterol enhance neuronal bioactivity and cell viability.…”
Section: Celastrus Paniculatusmentioning
confidence: 99%
“…The antioxidant and anti-Alzheimer activities of the crude methanolic extract of Celastrus paniculatus seeds were investigated. The extracts scavenged DPPH free radicals, inhibited peroxynitrite (ONOO−), and reduced ROS production [128] Coriandrum sativum In the tropical and subtropical region, Pakistan, and all South-East Asian countries [129] Ficus carica South Asian to Easter pedestrian Mesocarp and endocarp metabolites scavenged ROS. NMR profiling showed that aliphatic chemicals like γ-sitosterol enhance neuronal bioactivity and cell viability.…”
Section: Celastrus Paniculatusmentioning
confidence: 99%
“…Certain bioactive chemicals found in herbs and spices have been proved to have health advantages and to play an important role in human growth and development. The effect of these bioactive components on diseases such as cardiovascular disease, diabetes, hypertension, obesity, and osteoporosis has been well documented [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%